The use of VoiceThread as a multimodal digital platform to foster online students’ task engagement, communication and online community building - Chen, Julian; Bogachenko, Tetiana; Sims, Craig; Cooper, Martin (2020)
Offering online courses as a pathway to higher education degrees is growing worldwide, including Australia (Greenland & Moore, 2014; Open Universities Australia [OUA], 2018). This rapid growth is undergirded by the profound influence of globalization and economic potential of online instruction (Rovai & Downey, 2010). Distance education is more cost-effective (Reiach, Averbeck & Cassidy, 2012) and offers more flexibility and accessibility (Anderson, 2010; Evans & Pauling, 2010) as students and instructors are not restricted by their physical location and can participate anytime and from anywhere (Kresevic, Burant, Denton, Heath & Kypriotakis, 2011). In addition, the use of mobile phones, tablets and multimedia in course delivery may provide a competitive edge by making online courses more aligned with the learning styles of modern students who feel comfortable with small screens, daily engaging in “producing, commenting, sharing and classifying [their] own content” (Evans & Pauling, 2010, p. 207).